Observation of the Starting and Low Speed Behavior of Small Horizontal Axis Wind Turbine. (5th June 2014) - Khan, Sikandar; Shah, Kamran; Izhar-Ul-Haq,; Khan, Hamid; Ali, Sajid; Ahmad, Naveed; Abid, Muhammad; Ali, Haider; Ihsanullah,; Sher, Mazhar
Abstract : This paper describes the starting behavior of small horizontal axis wind turbines at high angles of attack and low Reynolds number. The unfavorable relative wind direction during the starting time leads to low starting torque and more idling time. Wind turbine models of sizes less than 5 meters were simulated at wind speed range of 2 m/s to 5 m/s. Wind turbines were modeled in Pro/E and based on the optimized designs given by MATLAB codes. Wind turbine models were simulated in ADAMS for improving the starting behavior. The models with high starting torques and less idling times were selected. The starting behavior was successfully improved and the optimized wind turbine models were able to produce more starting torque even at wind speeds less than 5 m/s.